PEMANFAATAN SUPERPLASTICIZER PADA BETON RINGAN STRUKTURAL BERAGREGAT LIMBAH BOTOL PLASTIK JENIS PET (POLY ETHYLENE TEREPHTHALATE) - Pratikto Pratikto (Jurnal Poli-Teknologi, 2011)
Abstract Selfweight of the structure is very dominant dwelling buildings to the earthquake load. The heavier building the greater of the inertia force due to self weight of the building. Own weight of concrete large enough to reach the density of 2400 kg/m3. Lightweight becomes an alternative to overcome the problem of its own weight because it has a density around 1700 kg/m3. Structural lightweight concrete category has the strength required more than 175 kg/cm2. This lightweight aggregate is obtained from waste plastic bottles that have a logo of PET. The plastic waste is the world's largest waste contributor and included into the class of materials that can not be described by the organism (non bio-degradable), and are durable (persistent) that does not rot. Plastic waste has a reduced weight and not easily change shape and waste PET plastic bottles (Poly Ethylene Terephthalate) can be used as coarse aggregate. This research is to find what is the ratio of the mixture of cement, coarse aggregate and fine aggregates and water along with oxygen enhancer admixture or additive that is suitable for the manufacture of lightweight structural concrete. Superplasticizer and silica fume is needed. A cylindrical test object to obtain the physical properties and mechanical properties of structural lightweight concrete Keywords: Lightweight Concrete, Waste PET plastic bottle, Weight own, lightweight aggregate.